Risk maps on ticks and tick-borne diseases in dromedaries in Tunisia - CGIAR Research Program on Livestock (2020)
First ever study in North Africa for the determination of sero and molecular prevalence of the CCHF virus in dromedaries and the associated potential public health risks.